Secretion of extracellular hsp90α via exosomes increases cancer cell motility: a role for plasminogen activation. - McCready, Jessica.; Sims, Jessica D.; Chan, Doug.; Jay, Daniel G. (2016)
Background: Metastasis is a multi-step process that is responsible for the majority of deaths in cancer patients. Current treatments are not effective in targeting metastasis. The molecular chaperone hsp90α is secreted from invasive cancer cells and activates MMP-2 to enhance invasiveness, required for the first step in metastasis.; Springer Open.